New earthworm records (Clitellata: Lumbricidae) from Bulgaria since 2012 - Valchovski, Hristo; Misirlioğlu, Mete; Valchovski, Hristo; Stojanović, Mirjana (Zootaxa, 2018)
The early scientists who studied the earthworm fauna of Bulgaria were Rosa (1897), Černosvitov (1934), and Mihailova (1966). Their work was continued by Šapkarev (1986) and Zicsi and Csuzdi (1986). In the last decade, researchers from Hungary, Serbia and Bulgaria organized explorations of many localities and enhanced the knowledge of the earthworm fauna of the country (Valchovski 2012, Stojanović et al. 2012, Szederjesi 2013). The present paper summarizes the new species records after these aforementioned three publications: Cernosvitovia munteniana, Eisenia andrei, Murchieona minuscula, Proctodrilus opisthoductus and Dendrobaena veneta.